Prefix Variation: A Comparison between Slang and Contemporary Standard Russian - Gjervold, Jonas (Poljarnyj vestnik, 2013)
This paper explores prefix variation in Russian occasional verbs. Occasional words are words that are produced in speech, but don't recur as consolidated units in the language. The main aim is to determine whether prefix variation behaves differently in occasional verbs than in standardized Russian.
Keywords: Russian; language; linguistics; verbs; prefixes